Tillage and herbicide reduction mitigate the gap between conventional and organic farming effects on foraging activity of insectivorous bats - Barré, Kévin; Le Viol, Isabelle; Julliard, Romain; Chiron, François; Kerbiriou, Christian (Ecology and Evolution, 2018)
International audience The increased use of pesticides and tillage intensification is known to negatively affect biodiversity. Changes in these agricultural practices such as herbicide and tillage reduction have variable effects among taxa, especially at the top of the trophic network including insectivorous bats. Very few studies compared the effects of agricultural practices on such taxa, and overall, only as a comparison of conventional versus organic farming without accurately accounting for underlying practices, especially in conventional where many alternatives exist. Divergent results founded in these previous studies could be driven by this lack of clarification about some unconsidered practices inside both conventional and organic systems. We simultaneously compared, over whole nights, bat activity on contiguous wheat fields of one organic and three conventional farming systems located in an intensive agricultural landscape. The studied organic fields (OT) used tillage (i.e., inversion of soil) without chemical inputs. In studied conventional fields, differences consisted of the following: tillage using few herbicides (T), conservation tillage (i.e., no inversion of soil) using few herbicides (CT), and conservation tillage using more herbicide (CTH), to control weeds. Using 64 recording sites (OT = 12; T = 21; CT = 13; CTH = 18), we sampled several sites per system placed inside the fields each night. We showed that bat activity was always higher in OT than in T systems for two (Pipistrellus kuhlii and Pipistrellus pipistrellus) of three species and for one (Pipistrellus spp.) of two genera, as well as greater species richness. The same results were found for the CT versus T system comparison. CTH system showed higher activity than T for only one genus (Pipistrellus spp.). We did not detect any differences between OT and CT systems, and CT showed higher activity than CTH system for only one species (Pipistrellus kuhlii). Activity in OT of Pipistrellus spp. was overall 3.6 and 9.3 times higher than CTH ...